Diet and Exercise Article RETRACTED due to manipulation by the authors The effectiveness of diet and exercise in the management of obesity - Nuridin Widya Pranoto; varhatun fauziah; Septriyan Anugrah; Gema Fitriady; Hendra Setyawan; Vlad Adrian Geantă; Alexandre Sibomana; Japhet Ndayisenga (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Background and objectives: Obesity is a growing global health problem and is becoming a significant challenge in the clinical and public health fields. One of the main concerns is the impact on an individual's quality of life. This review aims to evaluate the effectiveness of various interventions, including physical activity and diet, in the management of obesity. Methodology: The selected studies involved a population of adults who were obese (aged 18 years and over) and had made lifestyle modifications through pattern changes, eating, physical activity, or both. A total of 324 articles were screened, of which 25 were duplicates. After a screening process for suitability, 261 articles were excluded. A further 27 articles were excluded due to inappropriate study design or incomplete data. A total of 11 full-text articles were then reviewed and included in our analysis. The results showed that participants who followed a milk-based diet recorded a significant decrease in body weight of -1.16 kg (confidence interval -1.66, -0.66 kg; p < 0.001) as well as a decrease in body fat mass of -1.49 kg (confidence interval -2.06, -0.92 kg; p < 0.001). Participants who adopted an alternate day fasting (ADF) eating pattern achieved an average weight loss of -0.9% ± 0.6% in the low weight loss group and -9.9% ± 1.1% in the low weight loss group. Meanwhile, participants who restricted calorie intake (Caloric Restriction/CR) recorded a weight loss of -1.3% ± 0.7% in the low weight loss group and -9.2% ± 1.2% in the weight loss group tall body. Combining approximately 175 minutes of intense physical activity per week with a controlled diet results in significant weight loss of up to 5%. In conclusion, this systematic review confirms that the most effective approach in the management of obesity in adults is a combination of strength and cardiovascular training of at least 175 minutes per week and a low-calorie diet tailored to the individual's metabolic needs and health condition.